2014
DOI: 10.1007/978-3-319-12415-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Conservation of Energy with Dioxygen: Cytochrome c Oxidase

Abstract: Cytochrome c oxidase (CcO) is the terminal oxidase of cell respiration which reduces molecular oxygen (O₂) to H2O coupled with the proton pump. For elucidation of the mechanism of CcO, the three-dimensional location and chemical reactivity of each atom composing the functional sites have been extensively studied by various techniques, such as crystallography, vibrational and time-resolved electronic spectroscopy, since the X-ray structures (2.8 Å resolution) of bovine and bacterial CcO have been published in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…The results of our study suggested that high levels of UA in hepatocytes significantly reduced the SDH activity in the mitochondria, indicating that UA damages the mitochondrial membrane structure and inhibits mitochondrial energy metabolism. CCO is an essential enzyme that produces a proton gradient for ATP production during mitochondrial oxidative phosphorylation (Yoshikawa et al, 2015). The results of our study suggest that high levels of UA in hepatocytes significantly reduced CCO activity in the mitochondria.…”
Section: Discussionmentioning
confidence: 50%
“…The results of our study suggested that high levels of UA in hepatocytes significantly reduced the SDH activity in the mitochondria, indicating that UA damages the mitochondrial membrane structure and inhibits mitochondrial energy metabolism. CCO is an essential enzyme that produces a proton gradient for ATP production during mitochondrial oxidative phosphorylation (Yoshikawa et al, 2015). The results of our study suggest that high levels of UA in hepatocytes significantly reduced CCO activity in the mitochondria.…”
Section: Discussionmentioning
confidence: 50%
“…However, its functional role has been controversial, despite the fact that it was supported by mutagenesis studies of a hybrid bovine/human construct, demonstrating that mutations of residues along the Hchannel blocked proton translocation, whereas those along the D-channel did not (33). In addition, several detailed models have been proposed for proton translocation via the Hchannel, such as those involving the changes in the redox state of heme a (Redox Bohr effect) (34,35) and proton accumulation mechanisms (1,14,36,37), although their role in proton translocation has been disputed (38). Recently, a detailed analysis of the H-channel by molecular dynamics simulations was reported by Sharma et al (39).…”
Section: Discussionmentioning
confidence: 99%
“…Copper (Cu) is a transition metal that is required for many important cellular processes exploiting its redox properties, such as aerobic respiration (e.g., cytochrome c oxidases [Cox]) ( 1 ), oxidation of chemicals (e.g., multicopper oxidases) ( 2 ), and elimination of free oxygen radicals (e.g., Cu-Zn superoxide dismutases) ( 3 ). However, like many essential metals, excessive concentrations of Cu are toxic to cells.…”
Section: Introductionmentioning
confidence: 99%